Analysis Of The Application Of Calculations, Deposit And Reporting Of Value Added Tax (Vat) At Pt. Light Source Mega Blessing (E-Facturing Based) - Miska HK (Pustaka Digital Indonesia, 2022)
This study aims to identify and analyze the factors that cause differences in recording with the actual VAT calculation results, and to find out and analyze PT.Sumber Cahaya Mega Berkah experiencing delays in VAT reporting. Retrieval of data in this study is a general description of the company and data related to VAT. The method used in this research is descriptive analysis method, namely the method by collecting existing data in the company, Calculating the VAT Period and Reporting the VAT Period using VAT data from January 2019 to September 2020. The results of this study are the calculation of the value added tax of PT. Sumber Cahaya Mega Berkah, experienced a late report due to an invoice correction in 2019, in January, February, March. And the VAT calculation made by PT. Sumber Cahaya Mega blessing is not in accordance with the applicable law both in calculation and reporting.